Metformin mitigates fibrosis and glucose intolerance induced by doxorubicin in subcutaneous adipose tissue - Biondo, Luana A.; Batatinha, Helena A.; Souza, Camila O.; Teixeira, Alexandre A.S.; Silveira, Loreana S. [UNESP]; Alonso-Vale, Maria I.; Oyama, Lila M.; Alves, Michele J.; Seelaender, Marilia; Neto, José C.R. (Frontiers, 2018)
Doxorubicin (DX) is a chemotherapeutic drug that is used in clinical practice that promotes deleterious side effects in non-tumor tissues such as adipose tissue. We showed that DX leads to extensive damage in adipose tissue via a disruption in 5'-adenosine monophosphate-activated protein kinase (AMPK) and PPAR-gamma signaling. Thus, we investigated whether co-treatment with the biguanide drug metformin (MET) could prevent the side effects of DX through the activation of AMPK in adipose tissue. The goal of the present study was to verify the effects of DX and adjuvant MET treatment in subcutaneous adipose tissue (SAT) and to determine whether MET could protect against chemotherapy-induced side effects. C57/BL6 mice received DX hydrochloride (2.5 mg/kg) intraperitoneally 2 times per week for 2 weeks (DX), concomitantly or not, with MET administration (300 mg/kg oral daily) (DX + MET). The control group (CTRL) was pair-fed according to the food consumption of the DX group. After euthanasia, adipose tissue fat pads were collected, and SAT was extracted so that adipocytes could be isolated. Glucose uptake was then measured, and histological, gene, and protein analyses were performed. One-way analysis of variance was also performed, and significance was set to 5%. DX reduced retroperitoneal fat mass and epididymal pads and decreased glycemia. In cultured primary subcutaneous adipocytes, mice in the DX group had lower glucose uptake when stimulated with insulin compared with mice in the CTRL group. Adipocytes in the DX group exhibited a reduced area, perimeter, and diameter; decreased adiponectin secretion; and decreased fatty acid synthase gene expression. SAT from MET-treated mice also showed a reduction in collagen deposition. Treatment with MET prevented fibrosis and restored glucose uptake in SAT after insulin stimulation, yet the drug was unable to prevent other side effects of DX such as tissue loss and inflammatory response.
Keywords: Adipose tissue; Chemotherapy; Doxorubicin; Fibrosis; Glucose; Metformin